Konsep Ketuhanan Dalam Lontar Tutur Parakriya - Ni Wayan Yuni Astuti; Ida Bagus Putu Eka Suadnyana (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2020)
Religion is an essential part of human life, in fact it can contribute greatly in guiding people to face the waves of life. Entering the era of modernization, one aspect of this is reflected in social order and social relations. Many of the teachings of Hinduism are written on palm leaves which need to be preserved by digging and deepening the contents to be immediately conveyed to the people so that they can become biased among the community, in accordance with current developments. This type of research is qualitative because it is a text research or library research whose primary data source is Lontar Tutur Parakriya which has been transcribed into manuscript / text form. Literature study and interviews were used as data collection methods and then performed qualitative descriptive data processing. Besides that, the theory used in dissecting this problem is the hermeneutic theory to find the meaning or teachings contained in it. The results of this study aim to describe Lontar Tutur Parakriya, the concise contents of Lontar Tutur Parakriya, the main contents of Lontar Tutur Parakriya, namely: Divinity, yoga, Tri Guna and the relationship between Bhuana Agung and Bhuana Alit in this lontar. While the teachings studied are 1) the tattwa teaching is advices or advices to teach Hindus to be able to get immortal and spiritual perfection which is eternal (Moksa or Kenirwanaan).